2020
DOI: 10.1101/2020.05.02.074518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tcf21+mesenchymal cells contribute to testis somatic cell development, homeostasis, and regeneration

Abstract: 2 Highlights • Multipotent Tcf21 + MPs can differentiate into somatic testis cell types • Tcf21 + cells contribute to testis and ovary somatic cells during gonadal development • Tcf21 + cells replenish somatic cells of the aging testis and in response to tissue injury • Testis Tcf21 cells resemble resident fibroblast populations in multiple organs 3 Summary Testicular development and function relies on interactions between somatic cells and the germline, but similar to other organs, regenerative capacity decli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 113 publications
(148 reference statements)
1
7
0
Order By: Relevance
“…PMCs and LCs (Shen et al, 2020), while the fate of Wnt5a + progenitors is mainly restricted to FLCs and ALCs, as reported here.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…PMCs and LCs (Shen et al, 2020), while the fate of Wnt5a + progenitors is mainly restricted to FLCs and ALCs, as reported here.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with its expression profile, our findings confirm that Wnt5a + cells are true steroidogenic progenitors giving rise to most FLCs and ALCs. Other genes expressed in steroidogenic progenitors might also have been potential candidates to use for genetically tracing the lineage of these cells, including Nr5a1, Nr2f2/CouptfII, Pdgfra and Tcf21/Pod1 (Brennan et al, 2003;Shen et al, 2020). However, the expression of these genes is not restricted to the steroidogenic progenitors and they usually display a more widespread expression, either at earlier stages of development and/or in other cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PTMs and stromal cells were clustered into a single large cluster (Figure 1D) and PTMs are suggested to be derived from interstitial progenitors (Shen et al 2020) , PTMs and stromal cells were grouped together for subsequent analysis. Re-clustering of this cell group generated 10 clusters of cells (Supplementary Figure S11A and B).…”
Section: Stromal Cell Heterogeneity and Ptm Development During The Pementioning
confidence: 99%
“…They arise from LC progenitors located in the testicular interstitium (Davidoff et al, 2004;Barsoum et al, 2013;Shima et al, 2013;Kilcoyne et al, 2014;Ademi et al, 2020). Two recent studies showed that both fetal and adult Leydig cells derive from a common pool of progenitor cells originating from the gonadal surface epithelium and mesonephric mesenchymal cells present from fetal life (Ademi et al, 2020;Shen et al, 2020). Evidence also shows that a subset of FLCs dedifferentiate at fetal stages to serve as potential ALC stem cells (Shima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%